Pyrex 10.10 Model of pyrite oxidation on shelves over the Quaternary - Kölling, Martin (Supplement to: Kölling, Martin; Bouimetarhan, Ilham; Bowles, Marshall W; Felis, Thomas; Hinrichs, Kai-Uwe; Schulz, Michael; Zabel, Matthias (2019): Consistent CO2 release by pyrite oxidation on continental shelves prior to glacial terminations. Nature Geoscience, 12, 929-934, https://doi.org/10.1038/s41561-019-0465-9, 2019)
This worksheet comprises a forward model of pyrite oxidation on exposed shelves over the Quaternary. Assuming the acid generated by pyrite oxidation during glacial exposure of shelves is fully buffered by carbonate dissolution, it calculates the oxygen consumption and CO2 release forced by this process. As the length of interglacials is not long enough to fully restock the pyrite reservoir (= "acid capacitor"), pyrite is gradually leached from the shelf along a descending pyrite oxidation front. This way, CO2 release by this process is increasingly retarded throughout the Quaternary to occur at ever-lower sea level. File 5: model worksheet including the code which is implemented in Excel. We recommend using Excel 2003 for Windows to run the model File 6: animiated view of a model run (MP4 file) File 7: Result of the reference model run in Koelling et al (2019)
Keywords: "acid capacitor"; CO2 release; MPT; pyrite oxidation; sea level